2021
DOI: 10.18823/asiatefl.2021.18.4.5.1144
|View full text |Cite
|
Sign up to set email alerts
|

References and Conjunctions as Cohesive Devices in Chinese Undergraduate EFL Students’ Argumentative Essays

Abstract: The present study explored the use of references and conjunctions in 116 argumentative essays written by Chinese university EFL students. Mainly guided by Halliday and Hasan's (1976) model on cohesion, the study revealed the following major findings: (1) the participants used references more than conjunctions and tended to use demonstrative references and clause connectives and additive conjunctions most frequently in their argumentative essays, (2) high-quality essays had significantly more frequent use of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Moreover, some references and conjunctions are used very rarely [13]. A related study found that references are used more frequently than conjunctions in the compositions of Chinese college students, and the types of references used at different levels will also make differences [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some references and conjunctions are used very rarely [13]. A related study found that references are used more frequently than conjunctions in the compositions of Chinese college students, and the types of references used at different levels will also make differences [14].…”
Section: Introductionmentioning
confidence: 99%